The person of the therapist: therapists' personal characteristics as predictors of alliance and treatment outcomes. (17th February 2023) - Clements-Hickman, Alyssa L.; Reese, Robert J.
Abstract: Objective Studies examining the unique contribution that the therapist has on outcomes (i.e., "therapist effects") have increased in recent years. Therapist effects are believed to occur via how the therapist's interpersonal and intrapersonal qualities influence the therapeutic relationship, which in turn influences outcomes. The current study focused on the extent to which professional self-doubt, counseling self-efficacy, and humility are therapist qualities that influence treatment outcomes. Methods: Data were collected from 46 therapists at a multi-site community behavioral health organization. Therapists completed measures of therapist characteristics. Therapists' responses were matched with de-identified archival client data ( N  = 1, 817) that contained an outcome and alliance measure administered every session. Multilevel modeling was used to determine the extent to which therapists' personal characteristics predicted client outcomes. Results: Results of the unconditional model for the alliance measure indicated a lack of growth in alliance scores across treatment. Approximately 5% of the variance in rate of growth for treatment outcome was between therapists. When controlling for the effects of counseling self-efficacy, professional self-doubt was marginally significant. When counseling-self-efficacy was removed from the model, professional self-doubt was no longer marginally significant. Conclusion: The findings highlight the complexity of therapist effects and the need for future research on this topic.